Comprehensive analytical review of cybercrime and cyber policy in West Africa - Victor A. Adewopo; Sylvia Worlali Azumah; Mustapha Awinsongya Yakubu; Emmanuel Kojo Gyamfi; Murat Ozer; Nelly Elsayed (Journal of Electrical Systems and Information Technology)
Abstract Cybercrime is a growing concern in West Africa due to the increasing use of technology and Internet penetration in the region. Legal frameworks are essential for guiding the control of cybercrime. However, the implementation proves challenging for law enforcement agencies due to the absence of a dedicated and effective regional institutional follow-up mechanism. This study conducted a systematic literature review focusing on West Africa’s prevalence of cybercrime, governing policies, regulations, and methodologies for combating cybercrime. West Africa countries face significant cybercrime challenges, exacerbated by inadequate resources and a dearth of security experts. This study pinpoints potential cybercrime prevention strategies, such as leveraging the triage framework and broadening research to cover pivotal areas like cyber aggression and cyberbullying. Our research findings highlight the urgency for policymakers and law enforcement agencies to devise more efficient prevention strategies and policies. Overall, this study provides invaluable insights into the state of cybercrime in West Africa to guide the formulation of potent prevention and intervention strategies.